The Dynamite Press : a publishing house and book village in a historical and industrial precinct (Modderfontein) in northeast Johannesburg - Bakker, Karel Anthonie (University of Pretoria, 2013)
Dissertation MArch(Prof)--University of Pretoria, 2012.